1985
DOI: 10.1016/0035-9203(85)90066-5
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis in Sudan: the Abu Hamed focus

Abstract: The current status of onchocerciasis in Abu Hamed, Northern Province, Sudan, was studied. Of 208 persons attending out-patient clinics in villages in this region, 71 were microfilariae-positive on skin snips or had palpable nodules. Microfilariae and worms in nodules were identified as Onchocerca volvulus. No microfilariae were seen in peripheral blood. Most nodules and microfilariae were found in the pelvic region, but the intensity of infection was uniformly low (av. less than 3 mf/mg). Despite this, signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…In addition, we reported low levels of transmission based on the presence of L3 larvae in black flies that same year. 18 These reports indicated that the annual treatment regimen had achieved a high degree of onchocerciasis control in the area, with a considerable reduction in prevalence of dermal mf from the 34% to 37% reported in the mid-1980s, 7,27 but had not yet interrupted transmission. It is important to note, however, that coverage during the years where annual treatment was offered was inadequate (less than 65%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, we reported low levels of transmission based on the presence of L3 larvae in black flies that same year. 18 These reports indicated that the annual treatment regimen had achieved a high degree of onchocerciasis control in the area, with a considerable reduction in prevalence of dermal mf from the 34% to 37% reported in the mid-1980s, 7,27 but had not yet interrupted transmission. It is important to note, however, that coverage during the years where annual treatment was offered was inadequate (less than 65%).…”
Section: Discussionmentioning
confidence: 99%
“…17 Historic parasitological data evaluating the status of the disease in the Abu Hamed focus were reported in 1985. 7 In 2007, additional entomological, parasitological, and serological data were collected, concurrent with the onset of semiannual treatments. Entomological analysis revealed that low levels of disease transmission existed before the shift to semiannual treatment activities in the area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations